Dry-Season Snow Cover Losses in the Andes (18°-40°S) driven by Changes in Large-Scale Climate Modes - Cordero, Raul R.; Asencio, Valentina; Feron, Sarah; Damiani, Alessandro; Llanillo, Pedro J.; Sepulveda, Edgardo; Jorquera, Jose; Carrasco Cerda, Jorge Fernando; Casassa, Gino (My University, 2019)
The Andean snowpack is the primary source of water for many communities in South America. We have used Landsat imagery over the period 1986-2018 in order to assess the changes in the snow cover extent across a north-south transect of approximately 2,500 km (18 degrees-40 degrees S). Despite the significant interannual variability, here we show that the dry-season snow cover extent declined across the entire study area at an average rate of about -12% per decade. We also show that this decreasing trend is mainly driven by changes in the El Nino Southern Oscillation (ENSO), especially at latitudes lower than 34 degrees S. At higher latitudes (34 degrees-40 degrees S), where the El Nino signal is weaker, snow cover losses appear to be also influenced by the poleward migration of the westerly winds associated with the positive trend in the Southern Annular Mode (SAM).
Keywords: Snowpack